(untitled) (Journal of the College of Basic Education, 2022)
Increased interest in democracy at the end of the last century and the beginning of the current century after many countries adopted it as their political system, and this interest was reinforced through the adoption of curricula by higher education institutions that help in building trends and consolidating the correct understanding of them. Therefore, the importance of the current research stands out through identification On the attitudes of students of the College of Basic Education who studied democracy and those who did not study it in college, and the difference between them according to the variable of gender, specialization and stage of study, the study was based on a questionnaire prepared by the researcher to measure students’ attitudes towards democracy consisting of (46) items designed according to the Likert method with five alternatives to answer each A phrase, and after verifying its validity by presenting it to a committee of specialized experts and finding the discriminatory power of the paragraphs, (38) paragraphs were retained. As for the stability, it was found by means of half-partition, reaching (0.87). The questionnaire was applied to a simple random sample chosen from five Sections in the college amounted to (107) male and female students, and the results showed that there are positive trends towards democracy among students of the first and third stages, and there are statistically significant differences according to the The gender and specialization changed, and no differences appeared in the stage variable, and the researcher made some recommendations and suggestions.